Normal forms for linear Hamiltonian vector fields commuting with the action of a compact Lie group - Melbourne, Ian; Dellnitz, Michael (Mathematical Proceedings of the Cambridge Philosophical Society)
Abstract We obtain normal forms for infinitesimally symplectic matrices (or linear Hamiltonian vector fields) that commute with the symplectic action of a compact Lie group of symmetries. In doing so we extend Williamson's theorem on normal forms when there is no symmetry present. Using standard representation-theoretic results the symmetry can be factored out and we reduce to finding normal forms over a real division ring. There are three real division rings consisting of the real, complex and quaternionic numbers. Of these, only the real case is covered in Williamson's original work.